2022
DOI: 10.3389/fmicb.2022.957167
|View full text |Cite
|
Sign up to set email alerts
|

Acetic Acid Bacteria in Sour Beer Production: Friend or Foe?

Abstract: Beer is the result of a multistep brewing process, including a fermentation step using in general one specific yeast strain. Bacterial presence during beer production (or presence in the beer itself) is considered as bad, since bacteria cause spoilage, produce off-flavors, and/or turbidity. Although most problems in the past related to lack of hygiene and/or cleaning, bacteria do still cause problems nowadays. Despite this negative imago, certain bacteria play an irreplaceable role during fermentation and/or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 119 publications
1
8
0
Order By: Relevance
“…S7 ). This is consistent with studies from other fermented foods that have shown that AAB lower the pH of their environment (6, 7). The release of acetic acid and corresponding decrease in pH may inhibit the growth of other species and aid in AAB persistence (52).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…S7 ). This is consistent with studies from other fermented foods that have shown that AAB lower the pH of their environment (6, 7). The release of acetic acid and corresponding decrease in pH may inhibit the growth of other species and aid in AAB persistence (52).…”
Section: Resultssupporting
confidence: 92%
“…This group is well-recognized for the fermentation of vinegar ( A. pastuerianus (1)), kombucha ( Komagataeibacter spp. (35)), lambic beer ( A. lambici (6)), water kefir ( Acetobacter sicerae (7)), and cocoa ( A. pasteurianus commercially, A. ghanensis/senegalensis spontaneously (8)), among others. Broadly, AAB produce acidic flavor in lambic beer and vinegar, contribute to flavor and discourage germination in cocoa beans, and produce the cellulose component of “SCOBY” in kombucha (7).…”
Section: Introductionmentioning
confidence: 99%
“…However, in some specific brewery technologies, a well‐controlled acetic acid fermentation by Acetobacter spp. might lead to the production of sour beers (Bouchez & De Vuyst, 2022).…”
Section: Fermented Foods From the World A Taxonomic Characterisationmentioning
confidence: 99%
“…Cider is fermented from apple juice, while perry is a result of fermentation of pear juice.Sake is result of alcoholic fermentation of rice with water. Mead is formed by alcoholic fermentation of honey and water [13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%